Pengaruh locus of control, risk tolerance, financial wellbeing dan herding behavior Terhadap Keputusan Investasi pada Generasi Millenial dan Generasi Z Di Jawa Timur - Riqqotul Arifa; Ina Uswatun Nihaya (Universitas Negeri Surabaya, 2026)
This study examines the influence of locus of control, risk tolerance, financial wellbeing, and herding behavior on investment decisions among Millennials and Gen Z in East Java. As these generations enter a crucial stage of financial planning, they face various challenges in making sound investment decisions. A total of 175 respondents participated in this study, consisting of individuals actively investing in the capital market. The research applied Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the data. The results reveal that financial wellbeing and herding behavior significantly influence investment decisions in both generations. Internal locus of control significantly affects investment decisions among Millennials but not among Gen Z. In contrast, external locus of control and risk tolerance do not have a significant effect on investment decisions in either generation. These findings suggest that financial stability and the tendency to follow group decisions—particularly through social and digital media play essential roles in shaping the investment behavior of young investors. This study contributes to a deeper understanding of behavioral finance in younger generations and offers practical implications for improving financial literacy and developing more targeted investment strategies.